A review of the sources and pharmacological research of morroniside - Shi, Pengliang; Zheng, Bingqing; Zhang, Shiyao; Guo, Qingmei (Frontiers in Pharmacology, 2024)
Introduction Morroniside (Mor) is a bioactive compound found in Corni Fructus (CF) [Cornaceae; Cornus officinalis Siebold & Zucc.], which has been used as medicine and food in China, Korea, and Japan for over 2,000 years. This review summarizes recent progress on Mor, specifically focusing on its distribution, isolation, detection, and various pharmacological effects. Methods A literature survey on Mor was conducted using electronic databases such as PubMed, ScienceDirect, CNKI, and Google Scholar. After removing TCM prescription-related standards, medicinal herb processing-related research, and other irrelevant works of literature, we obtained relevant information on Mor’s biological and pharmacological properties. Results The main conclusions are as follows: Mor is widely distributed in the plant kingdom; the methods for extracting and isolating Mor are well established; and the technology for detecting it is accurate. Mor exhibits numerous pharmacological effects. Along with CF, Mor has shown renoprotective effects against diabetes, hepatoprotective effects against diabetes, triptolide, and nonalcoholic steatohepatitis, and boneprotective effects against osteoporosis and osteoarthritis. In addition, researchers have also explored other pharmacological effects of Mor, including neuroprotective effects against focal cerebral ischemia, spinal cord injury, and Alzheimer’s disease; cardioprotective effects against acute myocardial infarction; protection of the digestive system from gastritis, inflammatory bowel disease, and colitis; protection of the skin by promoting hair growth, wound healing, and flap survival; and protection of the lungs from acute lung injury and pulmonary fibrosis. Moreover, Mor has anti-obesity effects, anti-inflammatory effects in the eye, and improves follicular development. Discussion Overall, this review provides a comprehensive understanding of the pharmacological effects of Mor, from which the limitations of the current research can be understood, which will help facilitate future research.